Evaluasi Unjuk Kerja Alat Spektrofotometer UV-Vis Menggunakan Holmium Oksida dan Kalium Dikromat - Thorikul Huda; Cecep Sa'bana Rahmatillah; Yusuf Habibi (EKSAKTA: Journal of Sciences and Data Analysis, 2011)
The Evaluation of Hitachi U 2010 UV-Vis Spectrophometer performance using holmium glass  from  Starna  reference materials  and  potassium  dichromate  has  been  done.    The  aim  of investigation with holmium glass was to known wavelength work region at ultra violet and visible area,  potassium  dichromate  solution  used  to  known  photometric  performance  of  UV-Vis spectrophotometer.   The  result of  investigation used holmium glass showed wavelength peak at 241,  278,  287,  333,  360,  418,  445,  453, 459,  536  and  637  nm  regions, wich  it  is  similar with reference material.  The determination of photometric resulted by absorbance value measurement at  235,  275,  313  and  350  nm  were  0,746;  0,860;  0,294;  0,641  respectively.      The  result  of wavelength  and  photometric  investigation  showed  that Hitachi U  2010  spectrophotometer was proper to done and suitable with SR 03 KAN reference.  Keywords:  UV-Vis  Spectrophometer,  holmium  glass,  potassium  dichromate,  wavelength,